ANALISIS KESULITAN GURU DALAM PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 DI SEKOLAH DASAR - Annisa Suci Rahayu; Arsyi Rizqia Amalia; Luthfi Hamdani Maula (Jurnal PGSD, 2020)
The Purpose of this research describe the analysis of difficultie and efforts of teachers in online learning at SDN 4 Karangtengah Sukabumi. This study used descriptive qualitative method. Data collection techniques used online observation, interviews, and documentation. Data analysis techniques used in this study were data reduction, data presentation, and conclusion drawing/verification. The writer acts as a data collection instrument. The result showed that difficulties experienced by teachers in online learning during the Covid-19 Pandemic were, communication tools and internet networks that were less supportive, learning materials incomplete, and assessment. The efforts made by teachers in overcoming difficulties experienced by providing supportive internet access, diverse assginments, and collaboration with school principal, teachers, and parents of students. The impact after the effort was made was there were significant changes in online learning during the Covid-19 Pandemic. Keywords: Teacher Difficulties, Online Learning Process.